Participatory Communication in Development: Standardizing Majelis Taklim to Strengthen Community Organizational Capacity in Tanah Bumbu Regency - Siswanto Rawali; Muhammad Muthahari Ramadhani; Maya Sari Dewi; Indira Fitriliyani; Ambo Sakka (Universitas Darul Ulum, 2026)
This study examines participatory communication as a strategy for the institutional standardization of Majelis Taklim (Islamic study groups) in order to strengthen the organizational capacity of community-based religious institutions in Tanah Bumbu Regency. Using a qualitative case study approach, data were collected through in-depth interviews with 18 informants, two focus group discussions, participant observation, and institutional document analysis. Informants were selected purposively based on active involvement in organizational management and standardization processes. Data analysis followed the interactive model of Miles, Huberman, and Saldaña (2014), comprising data reduction, data display, and conclusion drawing, supported by triangulation and member checking. Findings reveal that participatory communication—encompassing dialogic forums, collaborative decision-making, information transparency, and multi-stakeholder engagement—plays a central role in constructing mutually agreed-upon institutional standards and strengthening governance, curriculum organization, and administrative systems. Da'wah communication, when practiced dialogically and contextually, functions as an instrument of social development by fostering collective awareness and social participation. Institutional standardization implemented through participatory mechanisms enhances managerial capacity, social legitimacy, and community trust. This study proposes a participatory communication model that integrates institutional strengthening with grassroots involvement, contributing to development communication theory with a religious-values-based framework.